N-Morpholine-N'-benzoylthiourea as an extractant for Pb(II) and Cu(II) in aqueous media: Crystal structure of bis(N-morpholine-N′-4-benzoylthioureato)lead(II) - Ifeanyieze, Kenechukwu Johncross; Okpareke, Obinna Chibueze; Oruma, Uchechukwu Susan; Ukwueze, Nkechinyere Nwanneka; Bircan, Ilknur Babahan; Asegbeloyin, Jonnie Niyi (European Journal of Chemistry, 2024)
The reaction of N-morpholine-N′-benzoylthiourea (L: HBMOR) and lead(II) acetate gave a neutral, stable metal(II) complex of type ML2. The Pb(II) complex crystallized in a monoclinic crystal system with P21/n space group. The complex was further characterized by spectroscopic and microanalytic analyses. The solvent extraction behaviors of Pb(II) and Cu(II) ions were investigated in aqueous media containing HBMOR/CHCl3 as extracting reagents. The solvent extraction of Pb(II) and Cu(II) ions from solutions of varying pH, varying concentrations of mineral acids (HCl, HNO3 and H2SO4), varying concentrations of masking agents (EDTA, KCN and KH[C8H6O4]) and varying concentrations of salting-out agents (NaCl, Na2SO4, KNO3) in chloroform solutions of HBMOR were studied. Pb(II) and Cu(II) ions were quantitatively extracted at pH = 7 in 10 min (HCl = 0.01 M) and pH = 8 in 5 min (H2SO4 = 0.01 M), respectively. The Pb(II) ions were quantitatively extracted with minimal interference from EDTA (0.01 M), KCN (0.50 M), and potassium hydrogen phthalate (1.0 M), while the Cu (II) ions were extracted with EDTA (1.0 M), KCN (1.0 M) and potassium hydrogen phthalate (0.01 M). The order of increasing interference for the extraction of Pb(II) and Cu(II) ions was KCN > potassium hydrogen phthalate > EDTA. Sodium sulfate (0.01 M) in HCl enhanced the extraction of Pb(II) ions, while sodium chloride (0.50 M) in HCl enhanced the extraction of Cu(II) ions. pH0.5 values of 0.67 and 2.70 were obtained for Pb(II) and Cu(II) ions, respectively, indicating that the separation of the two metal ions is favorable with HBMOR.